2018
DOI: 10.1038/s41467-018-03612-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical concentration using organic solvent forward osmosis for solvent recovery

Abstract: The organic solvent forward osmosis (OSFO) process can simultaneously concentrate the active pharmaceutical ingredients (APIs) and recover the organic solvents. Here we demonstrate and evaluate an OSFO process for solvent recovery. In this demonstration, OSFO was conducted in different solvents with different draw solutes. The OSFO process shows rejections >98% when recovering organic solvents from different feed solutions, even when the feed concentration is as high as 20 wt%. More importantly, all systems ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(105 citation statements)
references
References 47 publications
2
102
0
1
Order By: Relevance
“…Two research papers published results from forward osmosis experiments treating pharmaceutical liquids. Cui et al (2018) reported about FO experiments in which they used typical pharmaceutical solvents as FS, which usually contain pharmaceutical active ingredients (API) [ 130 ]. The aim was to recover the organic solvents and reject the API.…”
Section: Application Of Forward Osmosis Technology In Manufacturinmentioning
confidence: 99%
“…Two research papers published results from forward osmosis experiments treating pharmaceutical liquids. Cui et al (2018) reported about FO experiments in which they used typical pharmaceutical solvents as FS, which usually contain pharmaceutical active ingredients (API) [ 130 ]. The aim was to recover the organic solvents and reject the API.…”
Section: Application Of Forward Osmosis Technology In Manufacturinmentioning
confidence: 99%
“…As the transport resistance of the developed membrane was mainly determined by the polyamide selective layer, the thickness of the polyamide layer was applied here. The solubility of a membrane was measured using the solvent evaporation method as described previously 9 . Briefly, once the free-standing polyamide thin film was fabricated, it was dried in a vacuum oven to remove the moisture.…”
Section: Methodsmentioning
confidence: 99%
“…Among them, organic solvent nanofiltration (OSN) is widely studied but the high operating pressure and fouling tendency may increase the capital and operating costs 7 . Recently, a novel process, organic solvent forward osmosis (OSFO), which was initially proposed by Lively and Sholl 8 , and then demonstrated by Cui and Chung 9 , is promising to lower the fouling tendency and treat the highly concentrated feed solutions. Similar to forward osmosis (FO) in water reuse processes 10 , both valuable products and organic solvents can be recovered from pharmaceutical streams.…”
mentioning
confidence: 99%
“…Subsequently, the diluted draw solution may be regenerated by filtration, distillation, or evaporation. Since no external pressure is needed, OSFO offers a number of advantages over the pressure‐driven processes, such as lower fouling tendency and higher flux recovery, which would lower the operation and maintenance costs . In addition, OSFO is expected to be utilized in the challenging separations where the osmotic pressure of solvent is too high to be operated in the pressure‐driven process such as OSN and OSRO.…”
Section: Typical Membrane Separation Processmentioning
confidence: 99%